Xingbi Gel Ameliorates Allergic Rhinitis by Regulating IFN-γ Gene Promoter Methylation in CD4+ T Cells via the ERK-DNMT Pathway - Ai, Si; Lin, Yueyong; Zheng, Jian; Zhuang, Xiangli (Frontiers in Surgery, 2021)
Allergic rhinitis (AR) is a non-infectious chronic nasal mucosal disease mediated mainly by immunoglobulin E (IgE) after exposure to allergens, and is a common clinical disease. At present, studies on allergic rhinitis mainly focus on cytokines, IgE and its receptors, basophil, eosinophils, mast cells and related genes. Among them, the secretion imbalance of Thl/Th2 subgroup has been recognized as one of the important mechanisms of AR pathogenesis, and is currently a research hotspot in the world. Il-4 and IFN-γ are recognized as the most important cytokines in AR, secreted by Th2 and Th1 cells respectively.Il-4 and IFN-γ are antagonistic to each other in regulating IgE synthesis. In this study, we also found that ERKl/2 and phosphorylation expression were significantly increased in CD4+T lymphocytes of AR mice, which means that ERK signaling pathway in CD4+T lymphocytes of AR mice is involved in the occurrence and development of AR. The results also indicated that the expression of DNMTs increased. To further verify the correlation between ERK signaling pathway and DNMTs expression, we treated AR mice with the specific inhibitor of ERKl/2 signaling pathway PD98059. The results showed that defects of ERK signaling pathway were significantly positively correlated with the down-regulation of DNMTl expression. Drug treatment is the key to the treatment of allergic rhinitis, this research through the Xingbi gel after the intervention, the influence of joint mice serum IgE and AR behavior score, based on the role of IFN-γ gene expression and regulation of Thl/Th2 balance and ERK signaling pathway, research the Xingbi gel of AR, provide new way for prevention and treatment of allergic rhinitis.